2024
DOI: 10.1038/s41586-023-06897-6
|View full text |Cite
|
Sign up to set email alerts
|

Adding α,α-disubstituted and β-linked monomers to the genetic code of an organism

Daniel L. Dunkelmann,
Carlos Piedrafita,
Alexandre Dickson
et al.

Abstract: The genetic code of living cells has been reprogrammed to enable the site-specific incorporation of hundreds of non-canonical amino acids into proteins, and the encoded synthesis of non-canonical polymers and macrocyclic peptides and depsipeptides1–3. Current methods for engineering orthogonal aminoacyl-tRNA synthetases to acylate new monomers, as required for the expansion and reprogramming of the genetic code, rely on translational readouts and therefore require the monomers to be ribosomal substrates4–6. Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Such next-generation molecules provide strategies for improved biologic therapies, tools for bioremediation, and plastic-like materials that biodegrade. But progress toward sequence-defined non-protein materials l has been exceptionally slow. Although most elements of the translational machinery tolerate even wildly divergent α-amino acid side chains, altered backbones are tolerated predominantly in vitro , at small scale, under nonphysiological conditions, and with efficiencies and fidelities that have not been rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such next-generation molecules provide strategies for improved biologic therapies, tools for bioremediation, and plastic-like materials that biodegrade. But progress toward sequence-defined non-protein materials l has been exceptionally slow. Although most elements of the translational machinery tolerate even wildly divergent α-amino acid side chains, altered backbones are tolerated predominantly in vitro , at small scale, under nonphysiological conditions, and with efficiencies and fidelities that have not been rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite enormous interest in sequence-defined biomaterials containing non-α-amino acid monomers, progress towards their in vivo biosynthesis has been exceptionally slow. There exists one report in which a single β 2 -ester has been introduced into a protein using the wild-type E. coli ribosome in vitro , but there are no examples in which any β 2 -hydroxy acid has been introduced into a ribosomal product in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Schepartz et al demonstrated the ability to expand substrate scope to encode for a variety of backbone modifications, such as α-hydroxy, α-thio, and N -formyl amino acids . Also, Chin et al have devloped a novel tRNA display system to identify aminoacyl tRNA synthetases for β-amino acids, α,α-disubstituted-amino acids, and β-hydroxy acids . Subsequent integration of these suppression systems into phage display will allow for increased diversity of the displayed peptides and enhanced stability of the identified peptide ligands.…”
Section: Applications Of Genetic Code Expansion To Phage Displayed Pe...mentioning
confidence: 99%
“…222,223 Recently, a report by Dunkelmann and co-workers in 2024 demonstrated in vivo site-selective incorporation of three β 3 -AAs [β 3 -pBrAla, (S)-β 3 -(m-bromophenyl)alanine , (S)-β 3 -(m-trifluoromethyl)-L-phenylalanine] and one α,α-disubstituted amino acid [(S)-αmethyl-4-iodo-L-phenylalanine] into GFP(150UAG) using E. coli. 494 Compared to in vitro methodologies, there remains much room for improvement for in vivo peptide display platforms utilizing npMs, as many hit peptides have weak, micromolar activities and backbone-modifying npMs typically cannot be included. 495 As all current platforms only use a single npM during affinity maturation, the most likely area that could be significantly improved is the use of mutually orthogonal ARS/ tRNA pairs to incorporate multiple npMs into peptide libraries.…”
Section: In Vivo Expression Of Proteins and Peptides Containing Non-p...mentioning
confidence: 99%
“…174 Briefly, this specialized tRNA display selects for PylRS variants that acylate their cognate tRNAs with npMs, independent of ribosomal translation efficiency. 494 As such, there is significant potential for the rapid expansion of available npMs for in vivo genetic code manipulation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%